Iran’s turn to the east? The role of ideology in the Islamic Republic’s foreign policy in Central Asia (1990-2001) - Pegolo, V (2023)
This thesis investigates the ways in which Iran’s post-revolutionary ideology has contributed to shaping the foreign policy of the Islamic Republic towards Central Asia after the fall of the USSR (1990-2001). It asks to what extent ideology played a prominent role in shaping Iran’s initial foreign policy strategy towards the newly independent Central Asian republics, and to what extent it remained a relevant factor in Tehran’s policy shifts through the 1990s. This topic has been chosen with the aim of synthesising two unconnected schools of thought in the literature on Iranian foreign policy, where there has been a tendency to centre the study of Iran-Western relationship around ideology, while Iran-East relations are often seen through a political economy lens. This thesis advances a new theoretical model to study the interaction between Iran’s post-revolutionary ideology and its foreign policy, the Four Pillar Model. This is a morphological model inspired by Gidden’s structuration theory, which proposes Pan-Islamism, Pan-Iranism, Anti-Imperialism, and National Sovereignty as the four core elements of Iran’s ideology. The model is tested against three case studies: the dissolution of the USSR (1990-1992), the Tajik Civil War (1992-1997), and the insurgency of the Islamic Movement of Uzbekistan (1999-2001). This thesis claims that the internal contradictions in Iran’s ideology determined the emergence of a ‘dual-track policy’ in Central Asia in the 1990s. Though Iran’s foreign policy oscillated from Pan-Islamism to Pan-Iranism and back, both foreign policy approaches continued to co-exist, striving for primacy. This strife reflected the struggle between different interpretations of the identity of the Iranian regime, but it was also strongly influenced by geopolitical changes in the region. The increase in American involvement in Central Asia after 1995 and its effect on regional power alignments and energy markets were paramount in tilting the scales back in favour of Pan-Islamism.